Professionnalisation des modes de diffusion sur YouTube : pour une exploration des outils de mise en ligne - Robin Cauche (Mise au Point)
Most of the videos broadcasted on YouTube are monetized, hence they generate revenues: for the Californian company of course, but also for the users who create and upload those videos. The profiles of these users differ, from professional audiovisual production companies to a wide array of variously trained amateurs. A study of the technical tools provided by the website might teach us a lot about its users, but also about YouTube itself and its policies. In other words: how does the platform envision audiovisual production and online diffusion, under several modes of professionalization? In this article, I address YouTube’s wide range of uses and users, according to the criteria of their technical skills. Then I consider the technical tools provided by YouTube’s Creator Studio, in order to analyze how technical systems may have an impact on their usages – and vice-versa.